Monitoring Cu2+-binding to a DNA-clip-phen conjugate and metal-centered redox processes by a fluorescent reporter group - Sprödefeld, Arnd; Kiel, Alexander; Herten, Dirk-Peter; Krämer, Roland (Zeitschrift für anorganische und allgemeine Chemie, 2013)
A DNA conjugate of the bis-1,10-phenanthroline ligand Clip-phen was prepared and combined with a complementary, fluorescent reporter labeled DNA strand. In the resulting ds-DNA, the fluorescent reporter signals both the binding of Cu2+ ions to the Clip-phen moiety and the reduction to Cu+ by a change in fluorescence intensity. In preliminary single molecule fluorescence investigations, these processes appear to be observable on the level of individual molecules by single molecule fluorescence spectroscopy, but further validation and optimisation of the system is needed.
First published: 17 May 2013
Gesehen am 15.02.2022
Im Titel ist "2+" bei Cu hochgestellt